Thermodynamic and technological optimization of complex cryogenic insulation systems - Venturi, Valentina (Politechnika Wrocławska, 2019)
Futurę accelerators like the Futurę Circular Collider (FCC) under study at CERN, will be considerably larger than the Large Hadron Collider (LHC) presently in operation, with consequent increasing demands for cryogenically efficient cryostat solutions. MLI insulating systems remain the technology of choice for large accelerators due to the compromise they offer between thermal performance and cost-effectiveness. Thermal design solutions for cryostats can employ different combinations of thermal shields operating at intermediate temperatures, with optimally chosen MLI solutions. Data in literaturę is scarce for MLI performance at 4.2 K when operating with a thermal shield at a temperaturę between 60 K and 20 K. Therefore, a dedicated test program for the qualification of MLI samples is underway at CERN, exploring different MLI configurations, shielding radiative heat from 20-60 K to 4.2 K and with residual gas pressures between 10-6 and 10-4 mbar. This presentation will show all the steps done for optimizing the experimental setup that brought to the measurement of different systems in different degraded vacuum conditions as well as the mathematical approaches to predict the MLI performances.
Keywords: multilayer insulation; cryogenics; cryostat; refrigeration